From Ecological Disruption to Environmental Awareness: Palemahan Values in Roald Dahl's Billy and The Minpins - Kadek Sadwi Sawitriyunita Dewi; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti; Ni Nyoman Artini (International Journal of Language and Literature, 2026)
Environmental degradation and low ecological awareness among the younger generation highlight the importance of integrating environmental values into education. One possible approach was to integrate the Palemahan concept (the relationship between humans and nature) in children’s literature, particularly novels. This study analyzed how little Billy’s characterization in Billy and the Minpins by Roald Dahl represented Palemahan values. The method used was an interpretive qualitative method by Miles, Huberman, and Saldana (2014) involving data collection, data condensation, data display, and conclusion drawing. The findings showed three stages of Palemahan values: violation, punishment, and internalization. Violations included disrespecting plantations, reckless curiosity, and delayed ecological awareness. These led to punishment in the form of consequences such as risk awareness and ecological awareness, disruption, and consequences, which later developed into internalization, including ecological creativity, environmental awareness, life appreciation, ecological harmony, and harmony restoration. The result of this study confirmed that children’s literature could serve as an effective educational medium, and it is recommended that such literary works be used in character education to foster ecological awareness.